Learning interest of boys and girls of senior classes - Skrickutė , L. (Psichologija, 1969)
The article is written on the basis of results obtained from questioning, completing forms, observations and individual conversations with the pupils. 1,212 pupils from various urban and rural middle schools of Lithuania were questioned. The analysis of researching material revealed that the interest in all subjects of exact sciences (physics, chemistry, mathematics) is growing in senior classes and interest in all the humanities (literature, history and languages) diminishes in senior classes. It concerns the pupils of both sexes, but the larger percent of boys take interest in exact sciences in all forms, and on the contrary the girls are inclined towards humanities. The boys are mostly interested in history among the humanities. Already in the graduating form the majority of girls are mare concerned with chemistry. Similar differences are observed while comparing the reading interests of boys and girls. The girls are mostly interested in literature that makes influence on their feelings and emotions and the boys prefer reading popular scientific literature. The differences between the girls’ and boys’ interests in different subjects taught at school are explained as differences of psychics of both sexes. But in senior classes those differences are closely connected with pupils’ professional interests as well, which are forming under the influence of many social factors and not always depend merely upon the pupils’ bents.
Keywords: learning interest; gender; senior classes